Stand by-y-y to start engines - Gallery, Daniel V. (New York : W. W. Norton, 1966)
Twelve stories of giant practical jokes or tricky maneuvers played by various officers of the Navy--a Blue Angel pilot, a bright young Ensign, and various competitive Admirals--on other members of their service, the Army, and gentlemen of the press.
Keywords: United States. -- Navy -- Fiction; Humorous stories